2017
DOI: 10.1016/j.burns.2017.01.037
|View full text |Cite
|
Sign up to set email alerts
|

The effect of seasonality on burn incidence, severity and outcome in Central Malawi

Abstract: The results of this study demonstrate the year-round phenomenon of burns treated at our institution, and highlights the slight predominance of burns during the cold season. These data can be used to guide prevention strategies, with special attention to the implications of the increased burn incidence during the cold season. Though burn severity and mortality remain relatively unchanged between seasons, recognizing the seasonal variability in incidence of burns is critical for resource allocation in this low-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…As in previous studies, the most frequent cause of paediatric burn injuries in the current study was determined to be scalds . The major reasons for scalds have been reported to be low socioeconomic and education levels of the family and a high number of children in the home . The majority of the cases in the current study were from rural and suburban regions.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As in previous studies, the most frequent cause of paediatric burn injuries in the current study was determined to be scalds . The major reasons for scalds have been reported to be low socioeconomic and education levels of the family and a high number of children in the home . The majority of the cases in the current study were from rural and suburban regions.…”
Section: Discussionsupporting
confidence: 56%
“…Paediatric burn cases are the third most common cause of accidental mortality after vehicle accidents and drownings. Burn injuries in the first 10 years of life are a major cause of mortality and morbidity, which are actually preventable in nature . The results of the current study indicate that, with the exception of electricity and fire burn injuries, all other burn types are more frequently encountered in paediatric cases <5 years old.…”
Section: Discussionmentioning
confidence: 60%
“…This is concluded to be the cause of high number of flame and scald burns. 29,30 The current study revealed that there was a highly significant increase in number of cases in winter season than other seasons. Our results showed that the highest percentage of the cases of burn in years of 2015 (27.5%) and 2016 (31.6%) was found in winter.…”
Section: Discussionmentioning
confidence: 80%
“…The reason for this seasonality is not clear. There have been studies which showed a significant difference in the incidence of burns according to season, but mortality was not different between seasons 17,18 . A previous study in United States reported the seasonal variation in surgical outcomes, although it is not limited to burn patients 19 .…”
Section: Discussionmentioning
confidence: 99%